Gold-catalyzed synthesis of iodofulvenes - Nösel, Pascal; Lauterbach, Tobias; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Chemistry - a European journal, 2013)
We report the gold-catalyzed synthesis of highly functionalized iodofulvenes from iododialkynes under mild conditions. The catalytic cycle involves the formation of gold acetylides and vinylgold intermediates. These intermediates can then undergo an unprecedented iodine/gold exchange. This new pathway for catalyst transfer in dual gold catalysis opens up the possibility of highly regioselective transformations directed by the gold in the organogold intermediates. The resulting products are well suited for further metal-mediated coupling reactions, allowing the synthesis of extended π-systems.